Effect of Excitation Migration and Upconversion in Highly Erbium-doped Glass Micro-sphere Lasers - Hoi, Pham Van; Huy, Bui; Chi, Do Thuy (Communications in Physics, 2012)
Excitation migration and upconversion process in the Erbium-doped silica-alumina glass microsphere lasers with concentrations of 2500-4000 ppm were investigated in detail. The experiment shows that under 976 nm excitation, the intense of up-conversion emission at 523, 546 and 657 nm, corresponding to the transitions ^2H_11 / 2 → ^4I_15 / , ^4S_3 / 2 → ^4I_15 / 2, and ^4F_9 / 2 → ^4I_15 / 2, respectively, ^ depends on the erbium content, migration of excitation and pump power. The excitation migration has strongly influenced on the threshold and Red shift of lasing wavelength and migration-assisted up-conversion process leads to degraded amplification performance of microsphere lasers made by silica-alumina glasses with different contents of Er-ions.